#### Answer

g(0)=0

#### Work Step by Step

g(x)=$\frac{x^{2}+2x}{x+3}$
g(0)=$\frac{0^{2}+2*0}{0+3}$
g(0)=$\frac{0}{3}$=0

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

g(0)=0

g(x)=$\frac{x^{2}+2x}{x+3}$
g(0)=$\frac{0^{2}+2*0}{0+3}$
g(0)=$\frac{0}{3}$=0

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.